Cryogenic ion trap vibrational spectroscopy of hydrogen-bonded clusters relevant to atmospheric chemistry - Heine, Nadja; Asmis, Knut R. (International reviews in physical chemistry, 2015)
Recent advances in the gas phase vibrational spectroscopy of mass-selected ions are described, highlighting experiments on hydrogen-bonded (HBed) clusters relevant to atmospheric chemistry. The use of cryogenic ion traps in combination with the widely tunable and intense radiation from infrared free electron lasers has allowed for new molecular-level insights into the structure and other properties of HBed clusters. Advances and challenges in the interpretation of their vibrational action spectra, in particular, the importance of considering anharmonic effects, are described and discussed. The advantages of isomer-specific measurements relying exclusively on excitations within the vibrational manifold are also evaluated. The article concludes with an outlook on future challenges and perspectives.